Education in Mecca Al- Mukaramah during the reign of Al – Sharif Al – Hussein bin Ali (1916 – 1924) - The Hashemite schools as a model - - Al- Amoush, Anas Nayef; Al- Shraah, Ibrahim Faour (Journal of Humanities & Social Sciences, 2021)
This study aims to focus the light on the nature of education in Mecca Al- Mukaramah and interesting in it during the period of Al- Sharif Al- Hussein bin Ali (1916 – 1924) and declaration the establishment of the kingdom of Al- Hejaz until the end of the Hashemite rule by Al- Saud at the end of 1924 A.D; This study focuses on the most important schools were established in Mecca Al- Mukaramah during the period of Al- Sharif Al- Hussein bin Ali , and the private schools that continued to perform their scientific mission in this period. This study based on a variety of sources and studies, on top of which – an important and contemporary source – which is the Qiblah newspaper, which was published in Mecca Al- Mukaramah between the years (1916 – 1924 ).